Posted by michelle on Monday, October 8, 2012 at 11:35pm.
Find the derivative of the function
1)f(t)=tan(e^2t)+e^tan2t
f'(t)=
[im not quite sure with this. im assuming the implicit differentiation]
2) F(t)=e^(8tsin2t)
[for this one i got 2e^(8t)(4sin(2t)+cos(2t)) but it is incorrect.

calculus  Arnold, Tuesday, October 9, 2012 at 12:33am
1) f'(t)=2*e^2t*(sec(e^2t))^2 + 2*e^tan2t*(sec(2t))^2
2)F'(t)=e^(8tsin2t)*(8sin2t+18tcos(2t)) 
calculus  Steve, Tuesday, October 9, 2012 at 5:01am
#1: no impliocit, just use the chain rule
f=tan(u) + e^v
f' = sec^2(u) u' + e^v v'
= sec^2(e^2t) * 2e^2t + e^(tan2t) * sec^2(2t) * 2
#2: f = e^u
f' = u^u u'
= e^8tsin2t * (8sin2t + 16tcos2t)